Lipopolysaccharide-responsive beige-like anchor is involved in regulating NF-κB activation in B cells - Pérez-Pérez, Daniela; Fuentes-Pananá, Ezequiel M.; Flores-Hermenegildo, José Mizael; Romero-Ramirez, Hector; Santos-Argumedo, Leopoldo; Kilimann, Manfred W.; Rodríguez-Alba, Juan Carlos; Lopez-Herrera, Gabriela (Frontiers in Immunology, 2024)
Introduction Lipopolysaccharide-responsive and beige-like anchor (LRBA) is a scaffolding protein that interacts with proteins such as CTLA-4 and PKA, the importance of which has been determined in various cell types, including T regulatory cells, B cells, and renal cells. LRBA deficiency is associated with an inborn error in immunity characterized by immunodeficiency and autoimmunity. In addition to defects in T regulatory cells, patients with LRBA deficiency also exhibit B cell defects, such as reduced cell number, low memory B cells, hypogammaglobulinemia, impaired B cell proliferation, and increased autophagy. Although Lrba-/- mice do not exhibit the immunodeficiency observed in humans, responses to B cell receptors (BCR) in B cells have not been explored. Therefore, a murine model is for elucidating the mechanism of Lrba mechanism in B cells. Aim To compare and evaluate spleen-derived B cell responses to BCR crosslinking in C57BL6 Lrba-/- and Lrba+/+ mice. Materials and methods Spleen-derived B cells were obtained from 8 to 12-week-old mice. Subpopulations were determined by immunostaining and flow cytometry. BCR crosslinking was assessed by the F(ab’)2 anti-μ chain. Activation, proliferation and viability assays were performed using flow cytometry and protein phosphorylation was evaluated by immunoblotting. The nuclear localization of p65 was determined using confocal microscopy. Nur77 expression was evaluated by Western blot. Results Lrba-/- B cells showed an activated phenotype and a decreased proportion of transitional 1 B cells, and both proliferation and survival were affected after BCR crosslinking in the Lrba-/- mice. The NF-κB pathway exhibited a basal activation status of several components, resulting in increased activation of p50, p65, and IκBα, basal p50 activation was reduced by the Plcγ2 inhibitor U73122. BCR crosslinking in Lrba-/- B cells resulted in poor p50 phosphorylation and p65 nuclear localization. Increased levels of Nur77 were detected. Discussion These results indicate the importance of Lrba in controlling NF-κB activation driven by BCR. Basal activation of NF-κB could impact cellular processes, such as, activation, differentiation, proliferation, and maintenance of B cells after antigen encounter.